Influence of Audit Quality, Pattern of Loans Concentration and Company Size to Banking Loans (Agency Problem of Creditor – Debtor at Manufacture Company in Indonesia) - Ria, Ria; Nuryatno, Muhammad (International Journal of Economics and Financial Issues, 2018)
This study aims to analyze the influence of Audit Quality, Loan Concentration Pattern, and Company Size to Large of Loans. This research uses quantitative method with regression analysis model by stratified random sampling based on subsector strata in manufacturing company that go public in Indonesia Stock Exchange. This study shows that there is a positive and significant correlation between audit qualities to the loans, there is a negative and significant correlation between loan concentration patterns to the loans, there is a positive and significant correlation between company sizes on the loans and ROA, current ratio and age of the company can be a control variable to the loans Keywords: Audit Quality, Loan Concentration Pattern, Company Size, Loans JEL Classifications: M4, M41, M42